Differences in worst-case scenarios calculated by fixed length and rolling average methods in professional soccer match-play - Oliva-Lozano, J. M.; Martín-Fuentes, I.; Fortes, V.; Muyor, J. M. (Biology of Sport, 2021)
The aims of this study were to describe the worst-case scenarios (WCS) in professional soccer players calculated by fixed length and rolling average methods with regards to each playing position. This was done, firstly, by comparing total distance (TD covered in the WCS; secondly, by comparing high-speed running distance (HSRD); and thirdly, by comparing sprint distance (SPD). The study was conducted over a three-mesocycle competitive period. The WCS of three distance-related variables (TD, HSRD, SPD) in four time windows (1, 3, 5, 10 minutes) were calculated according to playing position (central defender; full-back; midfielder, wide midfielder, and forward) using fixed length and rolling average methods. A significant effect of the type of method used to calculate the WCS in TD (F(1, 142) = 151.49, p < 0.001, np2 = 0.52), HSRD (F(1, 138) = 336.95, p < 0.001, np2 = 0.71) and SPD (F(1, 138) = 76.74, p < 0.001, np2 = 0.36) was observed. In addition, there was a significant interaction between type of method and WCS duration in TD (F(1.36, 193.53) = 41.95, p < 0.001, np2 = 0.23), HSRD (F(2.28, 315.11) = 21.77, p < 0.001, np2 = 0.14) and SPD (F(2.59, 358.41) = 6.93, p < 0.001, np2 = 0.05). In conclusion, the use of fixed length methods of different durations significantly underestimated the WCS of TD, HSRD and SPD across the most common playing positions in professional soccer players. Therefore, the application of rolling averages is recommended for an appropriate WCS analysis in professional soccer match-play.